Internet Of Things : Mengotomatisasi Pemberian Makan Ikan Lele dengan Memantau Sistem Panel Surya Off-Grid - Gustiawan, Ridho; Sadi, Sumardi; Mulyati, Sri (Jurnal Teknik, 2024)
AbstractA very profitable business for catfish farming, besides the results can be eaten alone, the rest can be sold and become additional income for those who cultivate it. Fish feeding activities sometimes experience delays and are not in accordance with a predetermined schedule. Feeding is often delayed resulting in starving fish and cannibals. To prevent delays in feeding, an automatic fish feed tool was made that can regulate fish feed schedules using the internet of things with an electric power source using solar panels. This tool describes the OFF-GRID PLTS monitoring system as a power source and works using the Real-Time Clock (RTC) Module as a component needed to provide information about the time as well as provide a schedule for fish feed driven by a servo motor. Based on the test results, the entire solar panel device can produce 14.19 Wh of electrical energy and charging a battery with a capacity of 12V 3A takes 13.6 hours. The amount and weight of fish feed issued by the servo motor for 1 dose of fish feed is 2 grams with an angle of 50 degrees.Keywords: Servo Motor, Real-Time Clock (RTC), PLTS, Monitoring, ESP8266, Blynk.